1996
DOI: 10.1046/j.1469-0705.1996.07040275.x
|View full text |Cite
|
Sign up to set email alerts
|

Pathognomonic echo patterns of benign cystic teratomas of the ovary: classification, incidence and accuracy rate of sonographic diagnosis

Abstract: The great variability in the sonographic appearance of ovarian cystic teratomas poses difficulties for their diagnosis and classification. To overcome such difficulties, we have proposed a simplified classification of the pathognomonic echo patterns of ovarian cystic teratomas based on three basic types of echo pattern. In a prospective study of 118 echogenic adnexal masses, with postoperative histological confirmation, this classification enabled the correct diagnosis to be made in 115 cases (accuracy rate, 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0
4

Year Published

2000
2000
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(40 citation statements)
references
References 0 publications
1
35
0
4
Order By: Relevance
“…The sonographic criteria of dermoid cysts were already published. 10 Based on these criteria, the accuracy rate of the sonographic diagnosis of dermoid cysts reached 97.45%. We found that the mean tumor diameter was 57 mm (range, 30-95 mm) and was usually located on the right side (68.8%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sonographic criteria of dermoid cysts were already published. 10 Based on these criteria, the accuracy rate of the sonographic diagnosis of dermoid cysts reached 97.45%. We found that the mean tumor diameter was 57 mm (range, 30-95 mm) and was usually located on the right side (68.8%).…”
Section: Discussionmentioning
confidence: 99%
“…The criteria for sonographic diagnosis of dermoid cysts included the detection of one of the following signs in an adnexal mass: the presence of an echoic area or echoic bandlike strand in a hypoechoic medium or the appearance of a cystic structure with fat-fluid level. 10 The aim of this study was to evaluate the preoperative clinical and sonographic characteristics of struma ovarii and to compare them with those of ovarian dermoid cysts.…”
mentioning
confidence: 99%
“…All patients had a sonographic diagnosis of ODC, based on previously published criteria [15]. The characteristic echo patterns of a suspected ovarian cystic teratoma are classified into three major groups as follows: (Ia) an echogenic mass in which the borders of the tumor (including the one distal to the transducer) are clearly visible; (Ib) an echogenic mass in which most of the tumor is visible except its distal border; Caspi/Lerner-Geva/Dahan/Chetrit/Modan/ Hagay/Appelman (Ic) an echogenic mass in which only the border of the tumor proximal to the transducer is seen, producing a 'tip of an iceberg' effect; (II) the presence of echogenic particles in a hypoechoic medium, creating a 'mesh-like' appearance within the tumor, and (III) a cyst with fat-fluid level.…”
Section: Patientsmentioning
confidence: 99%
“…An incidence of 8.9/100,000/year was reported [3], although the actual prevalence of ODC is probably much higher. Familial cases of ODC have been reported, suggesting a possible genetic etiological factor [4][5][6][7][8][9][10][11][12][13][14][15]. In order to examine this association, we performed a casecontrol study comparing the prevalence of a history of ODC among first-degree relatives of women with and without ODC.…”
Section: Introductionmentioning
confidence: 99%
“…The false negative rate may be considered very low. The correlation of sonography features with histological diagnosis has been found to be high in some benign ovarian tumours such as endometrioma (AlcĂĄzar et al, 1997b), mature teratoma (Caspi et al, 1996), haemorrhagic cyst (Okai et al, 1994), simple cyst (Castillo et al, 2004), hydrosalpinx (Guerriero et al, 2000), peritoneal cyst (Guerriero et al, 2004) and cystadenofibroma (AlcĂĄzar et al, 2001a).…”
Section: Introductionmentioning
confidence: 99%